Performance Anxiety and Sport Training - Paprocki, D. A.
There are a number of books related to both music and athletics that cover some or all of the techniques that I have described. The Inner Game of Music by Barry Green, SyberVision by Steven and Greggory DeVore, and Peak Performance by Charles Garfield are three very detailed programs for enhancing performance through the use of goal setting, relaxation, and visualization or mental practice. In each book the authors do not suggest immediate solutions but present a program that would take several months to complete. Since a musician is physically limited to the amount of time he or she can perform or practice, that time should be used judiciously. By employing the various techniques that I have presented a musician/athlete can maximize performance without degrading physical condition through abnormally long practice or workout sessions. The athlete of the 21st century must possess a fit mind as well as body. This last statement can hold true for the musician as well, since the number of employment opportunities in performance have diminished while the number of qualified applicants has remained the same. A player can help turn the odds in his or her favor by having an edge in overall practice time (mental and physical), developing a coping mechanism for dealing with performance anxiety, and forming a strategy for arriving at one's goals.